Componentes agronômicos e índices fisiológicos da mandioca correlacionados ao preparo do solo - Figueiredo, Priscila Gonzales [UNESP] (2014)
The present study aimed to evaluate the correlation between the physical characteristics of the soil, promoted by different tillage, and the qualitative and quantitative agronomic traits and physiologic indexes of cassava pla nt and identify at what time of plant development these correlations imply in possible differences in agronomic components. A field experiment was carried out in a randomized block split plot design with six replications. The types of tillage (minimum till age, conventional tillage and no tillage) were considered main plots and the times of evaluation, the subplots. The results, except for physiological indexes, were subjected to analysis of variance at 5% level of probability by F test, the treatments were compared by t test at 5% probability and times of evaluation were compared by regression. Additionally, all parameters were correlated by the Pearson coefficient. It was observed that the greater resistance to soil penetration in no tillage was a factor th at determined the larger partition of dry matter in the shoot rather than the roots ; in this treatment, the productivity of dry matter in the roots, at 210, 300, 330 and 360 days after planting (DAP), was about 2000 kg ha - 1 lower than for the other types o f tillage. It was concluded that the soil 's physical characteristics correlate with the qualitative and quantitative agronomic characters and do not correlate with the physiological ind exe s. These correlations imply qualitative differences from 120 DAP and quantitative differences from 150 DAP, and that macroporosity, total porosity and penetration resistance correlate directly with the productivity of dry mass of shoots...